Características de los cursos de investigación en escuelas de medicina del Perú - Taype Rondán, Á (2015)
Aim: To evaluate the research courses’ characteristics and the scientific output of its teachers within Peruvian medical schools. Methods: A cross-sectional descriptive study was performed, using data from the medical schools existing in Peru in 2011. The research courses’ syllabi and its teachers were evaluated. The number of courses, its teachers and the scientific output of them were assessed. Results: Schools had a median of 5.5 [range 2 to 18] credits of research courses, and 1.75% [0.6 to 6.3] was the median of percentages of total credits. In 18/32 (56%) schools existed at least one course requiring the student to present a final inform, and only one school entailed the students to publish the courses’ products in scientific journals. Furthermore, only five (16%) schools employed at least one instructor that had ever published at least one original article as the corresponding author in a Scopus-indexed journal. Conclusion: Peruvian medical schools’ research courses do not include the publication process as a targeted skill and its teachers have a poor scientific output.